2021
DOI: 10.3389/fped.2021.734540
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cytokine Endotoxin Responses in Neonatal Encephalopathy Predict MRI Outcomes

Abstract: Background: Neonatal encephalopathy (NE) is associated with adverse neurodevelopmental outcome and is linked with systemic inflammation. Pro-inflammatory and anti-inflammatory cytokines are known to play a role in the pathology of NE by activating innate immune cells.Methods: Eighty-seven infants were enrolled including 53 infants with NE of whom 52 received therapeutic hypothermia (TH) and 34 term infant healthy controls (TC). Whole blood sampling was performed in the first 4 days of life, and a 14-spot ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Understanding the role of cytokines in the evolution of neonatal brain injury, as well as the dynamic nature of cytokine release after a hypoxic-ischemic insult, is a promising avenue for identifying biomarkers of ongoing brain injury in newborns with antenatal/postnatal infection/inflammation following HI, especially those that do not show an improved outcome after TH [84,[104][105][106][107].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the role of cytokines in the evolution of neonatal brain injury, as well as the dynamic nature of cytokine release after a hypoxic-ischemic insult, is a promising avenue for identifying biomarkers of ongoing brain injury in newborns with antenatal/postnatal infection/inflammation following HI, especially those that do not show an improved outcome after TH [84,[104][105][106][107].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, O'Dea et al reported relative immune hyporesponsiveness to endotoxin challenge among infants with NE with elevated cytokine levels. 68 Additional therapies targeting immunomodulation such as azithromycin 69,70 may complement the neuroprotective effect of melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…These excessively high cytokine levels, leading to overwhelming immune hyperactivation, may impair the ability of melatonin to modulate the immune response. Indeed, O'Dea et al reported relative immune hypo‐responsiveness to endotoxin challenge among infants with NE with elevated cytokine levels 68 . Additional therapies targeting immunomodulation such as azithromycin 69,70 may complement the neuroprotective effect of melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…Serum Epo levels are significantly elevated in both term and preterm infants with adverse neurodevelopmental outcomes and remain dysregulated in later childhood post-NE. 3,[90][91][92][93] Recombinant Epo may upregulate Epo receptors in animal models of neonatal HI and Epo levels for tissue protection may be up to 1000-fold higher than required for erythropoiesis. 94 Numerous studies of Epo neuroprotection performed in rodents, sheep, and nonhuman primates have provided consistent evidence that exogenous Epo results in both histologic and functional benefit, with most benefit seen in multiple, high-dose treatment regimens.…”
Section: Seizure Managementmentioning
confidence: 99%
“…Serum Epo levels are significantly elevated in both term and preterm infants with adverse neurodevelopmental outcomes and remain dysregulated in later childhood post-NE. 3 , 90 93 Recombinant Epo may upregulate Epo receptors in animal models of neonatal HI and Epo levels for tissue protection may be up to 1000-fold higher than required for erythropoiesis. 94 …”
Section: Erythropoietin In Term Infantsmentioning
confidence: 99%